Coffee consumption and alertness: a study among office workers in Jakarta - Herqutanto,; Rosemiarti, Tria; Dewi, Dian Kusuma; Soemarko, Dewi Sumaryani; Syam, Ari Fahrial (Frontiers in Nutrition, 2024)
Background Coffee is widely consumed by office workers, primarily for its caffeine content, which plays an important role in improving alertness. For white-collar workers, alertness is crucial to maintaining productivity, and one measurable parameter of alertness is reaction time. Changes in reaction time can be classified as either shorter or longer compared to the initial measurement taken before coffee consumption, with a longer reaction indicating a decrease in alertness. The objective of this study is to investigate the relationship between coffee consumption and improvements in alertness. Materials and methods This cross-sectional study compared coffee drinkers and non-coffee drinkers, assessing their alertness using the Lakassidaya tool and collecting data on coffee consumption and caffeine intake through a 7-day fluid diary. Alertness was measured in the morning (baseline) and 30 min after coffee consumption (end line). Study participants were office workers from a company in Jakarta, Indonesia. Results A total of 121 participants completed the study, with 47.1% (n = 57) of them being coffee drinkers. No significant differences were found in the characteristics of the respondents. The average daily coffee consumption among these workers was 247 (157–391) mL/day, with a caffeine intake of 72 (36–121) mg/day, which was below the minimum amount typically required to trigger a positive alertness reaction. There was no significant association between coffee consumption and alertness (OR = 1.538, 95% CI: 0.288–1.467, p = 0.403), nor was there a significant difference in the change in reaction time between coffee drinkers and non-coffee drinkers (17.3 [1.4–32.2] ms vs. 13.0 [−3.9–26.0] ms, p-value = 0.111). However, there was a trend toward improved alertness in coffee drinkers, as indicated by shorter reaction times at baseline (180 [160–195.2] ms) compared to post-consumption (155 [146.6–170.2] ms). Conclusion There was no significant association between coffee consumption and alertness improvement between coffee drinkers and non-coffee drinkers among office workers in Jakarta, Indonesia.